Evaluasi dan Perbandingan Kinerja Manajemen Gudang di Garut Menggunakan Integrasi Metode AHP-SAW - Hatala, Muhammad Hudzaly; Fatliana, Anggun Nindy; Rahmad, Nuraini; Walenna, A. M. Adhitya A.; Krisnasari, Dea Dita; Salma, Melati; Mardika, Riski Arif; Putra, Azhar Syafiq (Jurnal Kalibrasi, 2025)
This study aims to evaluate and compare warehouse management performance in Garut Regency based on five main variables: warehouse layout, equipment, SOP standards, human resources (HR), and occupational health and safety (K3). A mixed-method approach was applied, where the Analytical Hierarchy Process (AHP) was used to determine the weight of each variable, while the Simple Additive Weighting (SAW) method was employed to calculate the total performance score (utility score) and rank warehouses according to the weighted scores of each variable. Data were collected from eight different warehouses through direct observation, interviews, and warehouse check-up audits using a Likert scale. The results show that warehouse layout holds the highest weight at 44.95%, followed by SOP at 23.67%, equipment at 15.02%, HR at 9.75%, and K3 at 6.62%. Warehouse 5 achieved the highest performance score of 94%, indicating the most optimal warehouse management due to its strong performance in layout and K3, as well as high utility scores in the other variables. In contrast, Warehouse 6 obtained the lowest score of 58%, mainly due to poor layout, limited equipment, and weak SOP, highlighting the need for significant improvements. These findings emphasize that layout and SOP are the most dominant factors in determining warehouse management effectiveness, while the other variables serve as supporting elements. The results also indicate that larger-scale companies tend to achieve higher utility scores, reflecting greater maturity across the five evaluated variables.